Association of Serum Ferritin with C Reactive Protein in Iron Deficiency Anaemia - Kiran Aamir, Sidrah, Safian Ahmed, Haji Muhammad Aftab Alam, Durga Devi, Aqsa Junejo, Aamir Ramzan, Farhan Ahmed Shaikh, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to determine whether or not individuals with iron deficiency anemia and an underlying inflammatory condition had a connection between serum ferritin as an acute phase reactant and C - reactive protein. Study Design: Cross-sectional/Prospective study Place and Duration: Liaquat university of Medical and health sciences jamshoro Hyderabad. January 2022 to December 2022 Methods: This research comprised 136 individuals who were suffering from iron deficiency anemia. After getting informed written consent detailed demographics of enrolled cases were recorded. Using an automated hematology analyzer (Mindray BC-5000), the parameters of the blood were analyzed. Serum ferritin levels were used to classify each patient into one of three categories. Serum ferritin levels were divided into three groups: Group I (serum ferritin <10 μg/L), Group II (11–150 μg/L), and Group III (>150 μg/L).SPSS version 23.0 was used to analyze the data. Statistical analysis was conducted using Pearson's correlation tests. Results: In current study patients mean age was 31.13±6.75 years and had mean BMI 24.6±3.52 kg/m2. There were majority 74 (54.4%) males and 62 (45.6%) females in this study. Majority of the patients 81 (59.6%) were had low ferritin <10 μg/L, followed by normal ferritin 11–150 μg/L in 45 (33.1%) cases and 10 (7.4%) cases had high ferritin >150 μg/L. We found strong co-relation of C reactive protein and high level of serum ferritin with p value <0.002. Serum ferritin levels were negatively correlated with hemoglobin. Conclusion: We concluded in this study that levels of serum ferritin was positively associated with C-reactive protein (CRP). In patients with underlying deficiency of iron, secondary inflammation may increase the level of ferritin in serum. Keywords: Ferritin, Haemoglobin, Iron Deficiency Anaemia, C-Reactive Protein